Computer Laboratory Management In Improving Students' Hard Skills In The Field Of Multimedia - Istifadah, Urfa Nailul; ‘Azah, Nur (Ar-Rosikhun: Jurnal Manajemen Pendidikan Islam, 2023)
The computer laboratory is a support for learning, skills and school infrastructure. Then required planning, organizing, implementation and evaluation. To make the computer laboratory directed and managerial so that the goal of procuring a computer laboratory is achieved effectively and efficiently. As for improving the hard skills themselves, it requires teaching that is repeated consistently and always evaluates so that the hard skills are even better. This research is included in qualitative research with a descriptive approach, the data collection methods used are interviews, observation and documentation. The key informant in this research is the head of the computer laboratory. While the supporting informants were the Head of School, Deputy Head of School for Facilities and Infrastructure, Deputy Head of School for Curriculum, and students. This research was conducted at MAN 1 Jombang. Based on the results of research on computer laboratory management including planning activities or goals for managing computer laboratories as well as organizing which includes the selection of good human resources and the preparation of organizational structures, the implementation of evaluation which is a managerial activity here also describes how to increase hard skills in the multimedia field. It also describes the supporting and inhibiting factors in managing computer laboratories in improving students' hard skills in the field of multimedia at MAN 1 Jombang.